A One-Session Treatment of PTSD After Single Sexual Assault Trauma. A Pilot Study of the WONSA MLI Project: A Randomized Controlled Trial - Rajan, Gita (Journal of interpersonal violence, 2022)
Sexual abuse is a crime with devastating health consequences. Accessible, acceptable and affordable treatment of PTSD after sexual abuse is important. In this pilot study, a one-session PTSD treatment and a modified perspective to PTSD treatment is introduced. The aim of the study was to test the efficacy of one session of Modified Lifespan Integration (MLI) on reduction of symptoms of PTSD in individuals with PTSD after one sexual assault. This was a single-center, individually randomized waitlist-controlled treatment study with 1:1 allocation, with the intervention of one 90 - 140 minutes session of MLI and with post-treatment follow-up at 3 weeks (time point two). All participants were females, mean age 24, with PTSD symptoms after one sexual assault during the past 5 years. Exclusion criteria were poor understanding of Swedish, multiple traumas, active substance abuse, active psychosis, ADHD, or autism spectrum disorder. Of 135 interested participants, 38 were finally included, 36 completed baseline measures and were included in the intent to treat analyses and 33 were analyzed per protocol. The primary outcome was the difference between the two trial arms in mean PTSD symptoms as measured by the Impact of Event Scale Revised (IES-R) at time point two. In the intervention arm, 72% no longer scored PTSD in per-protocol analysis, compared to 6% in the waiting list arm. IES-R scores were on average halved in the intervention arm (F=21.37, P<0.001), but were essentially unchanged in the waiting list arm. No adverse effects or drop-outs were seen. One session of Modified Lifespan Integration was an effective treatment with a low drop-out rate for females aged 15-65 with PTSD after one sexual assault. Provided that this result can be replicated, MLI should be offered to these patients in clinical settings. Registration number NCT03141047 was given 03/25/2016 at ClinicalTrials.gov (https://register.clinicaltrials.gov/).